A DFX-based iron nanochelator for cancer therapy - Liu, Peng; Wang, Qiang; Li, Kuan; Bi, Bo; Wen, Ying-Fei; Qiu, Miao-Juan; Zhao, Jing; Li, Bin-Bin; Zhang, Chang-Hua; He, Yu-Long (Frontiers in Bioengineering and Biotechnology, 2022)
Iron as an essential element, is involved in various cellular functions and maintaining cell viability, cancer cell is more dependent on iron than normal cell due to its chief characteristic of hyper-proliferation. Despite that some of the iron chelators exhibited potent and broad antitumor activity, severe systemic toxicities have limited their clinical application. Polyaminoacids, as both drug-delivery platform and therapeutic agents, have attracted great interests owing to their different medical applications and biocompatibility. Herein, we have developed a novel iron nanochelator PL-DFX, which composed of deferasirox and hyperbranched polylysine. PL-DFX has higher cytotoxicity than DFX and this effect can be partially reversed by Fe2+ supplementation. PL-DFX also inhibited migration and invasion of cancer cells, interfere with iron metabolism, induce phase G1/S arrest and depolarize mitochondria membrane potential. Additionally, the anti-tumor potency of PL-DFX was also supported by organoids derived from clinical specimens. In this study, DFX-based iron nanochelator has provided a promising and prospective strategy for cancer therapy via iron metabolism disruption.